2016
DOI: 10.1152/ajpendo.00400.2015
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide exerts direct protective effects on endothelial cells through the AMPK/Akt/eNOS pathway in a GLP-1 receptor-dependent manner

Abstract: Glucagon-like peptide-1 (GLP-1) may have direct favorable effects on cardiovascular system. The aim of this study was to investigate the effects of the GLP-1 analog exenatide on improving coronary endothelial function in patients with type 2 diabetes and to investigate the underlying mechanisms. The newly diagnosed type 2 diabetic subjects were enrolled and given either lifestyle intervention or lifestyle intervention plus exenatide treatment. After 12-wk treatment, coronary flow velocity reserve (CFVR), an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 40 publications
(53 reference statements)
2
61
1
Order By: Relevance
“…GLP‐1 has an advantage to stimulate glucose‐dependent insulin secretion, therefore avoiding the side effects such as hypoglycemia that traditional diabetic drugs may cause, suggesting that GLP‐1R‐activating reagents are potential agents for alleviating T2DM and its associated complications . Activation of ERK1/2 and PI3K/Akt, and AMPK/Sirt‐1 signaling has been considered as major mechanisms accounting for the beneficial effects of GLP‐1R . Accordingly, induction of GLP‐1R can enhance the transcription of PDX‐1 through activation of these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…GLP‐1 has an advantage to stimulate glucose‐dependent insulin secretion, therefore avoiding the side effects such as hypoglycemia that traditional diabetic drugs may cause, suggesting that GLP‐1R‐activating reagents are potential agents for alleviating T2DM and its associated complications . Activation of ERK1/2 and PI3K/Akt, and AMPK/Sirt‐1 signaling has been considered as major mechanisms accounting for the beneficial effects of GLP‐1R . Accordingly, induction of GLP‐1R can enhance the transcription of PDX‐1 through activation of these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it is questionable whether the required micromolar concentrations of P-site inhibitors can be obtained in the intact organism without off-target effects (Seifert, 2016). Overall, NKY80, SQ22,536, and vidarabine, which are very widely used as "selective mAC inhibitors" (or even more problematic as "selective AC5 inhibitors") (e.g., Rangel-Barajas et al, 2011; Bravo et al, 2016;Liu and Steketee, 2016;Wada et al, 2016;Wei et al, 2016), should be used with great caution as pharmacological tools, and any observed effects should be carefully checked for off-target actions (Seifert, 2014(Seifert, , 2016. It is particularly important to confirm that the AC inhibitor used actually prevents a GPCR-or FSKmediated cAMP increase (Brunskole Hummel et al, 2013).…”
Section: +mentioning
confidence: 99%
“…These results suggest that AMPK/eNOS signaling pathway is involved in madagascine-induced vasodilatation ( Figure 4 ). Both AMPK/eNOS and AMPK/AKT/eNOS are known to be related to increase the production of NO (Bradley et al, 2010; Wei et al, 2016). As shown in Figure 5 , madagascine-induced vasodilatation in the presence of SC66 was more transient than that in the absence of SC66.…”
Section: Resultsmentioning
confidence: 99%